Analisis Strategi Pengembangan UMKM Untuk Meningkatkan Daya Saing Industri Rumah Tangga Dempo Pisang Kecamatan Poleang Timur Kabupaten Bombana - Marnida Marnida; Suwarto Suwarto; Niar Astaginy (Manajemen Kreatif Jurnal, 2023)
This research aims to determine the potential and obstacles in developing the Dempo Banana home industry in Bombana Regency. The reason for choosing the research topic is that the commodity in Bombana Regency is bananas, which makes the banana demo product a typical snack in Bombana Regency which still needs to be developed. And to develop a development strategy, the type of research used is descriptive qualitative, namely an analysis used to describe or solve problems systematically using the SWOT analysis method, namely an analysis intended to see the extent of the implementation of the Dempo Banana Home Industry Development Strategy based on strengths, Weaknesses, Opportunities and Threats, after analyzing the four SWOT indicators, we then developed appropriate alternative strategies to be applied to the domestic banana dumpling industry. The results of this research show that strategies that can be implemented include: (A). Utilizing Capital Assistance from the Government to Support the Development of the Dempo Banana Home Industry. (b). Utilizing the special characteristics of Banana Dempo as a typical banana snack that is famous throughout Indonesia. (C). Utilizing the Abundant Availability of Raw Materials as a Means of Running a Production Process That Supports Product Availability in the Industry. (D). Maintain consumer/customer loyalty by maintaining the quality of existing products and continuing to innovate so that consumers do not get bored with the taste, appearance and quality of the product. (E). Must maintain good product quality in terms of hygiene, halal, packaging and price so that customers do not Turn to Other Products.